Understanding the Dynamics of Turnover Intention: The Role of Job Satisfaction Mediation in the Relationship Between Resilience, Job Security, and Leadership - Maria Niasty, Titi; Widhiastuti, Hardani; Dewi, Rusmalia (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The company needed to pay attention to and retain employees to prevent turnover intention that could arise due to a lack of attention from the company or insufficient comfort in the workplace. The vacant positions left by departing employees required other employees to fill the gaps or take on double jobs, along with additional costs for recruiting new employees with the skills and competencies needed by the company. This study aimed to fill the gap in the literature by examining the influence of resilience, job security, and leadership on turnover intention, mediated by job satisfaction, in the context of Generation Z employees in the hospitality industry. The research employed a quantitative method, with data analysis using Smart PLS SEM (Partial Least Squares - Structural Equation Modeling) software. The results showed that resilience, job security, leadership, and job satisfaction had a significant influence on turnover intention among Generation Z employees. Employees with higher resilience, a sense of job security, effective leadership support, and adequate job satisfaction were less likely to have turnover intention. The practical implication of this study is that organizations need to develop programs focused on enhancing resilience, effective leadership, and job satisfaction, as well as ensuring clear job security to increase employee retention and long-term productivity. Perusahaan harus memperhatikan dan memelihara karyawan agar tidak memiliki keinginan untuk pindah atau turnover intention yang muncul akibat kurangnya perhatian dari perusahaan atau kurangnya kenyamanan di tempat kerja. Kekosongan posisi yang ditinggalkan karyawan sehingga karyawan lain dituntut mengisi posisi kosong atau menjalani double job serta biaya tambahan untuk merekrut karyawan baru yang memiliki kualitas dan kemampuan sesuai dengan kebutuhan perusahaan. Penelitian ini bertujuan untuk mengisi gap dalam literatur dengan meneliti pengaruh resiliensi keamanan pekerjaan dan kepemimpinan terhadap turnover intention yang dimediasi oleh kepuasan kerja dalam konteks karyawan generasi Z di industri perhotelan. Metode penelitian ini yang digunakan adalah penelitian kuantitatif Dengan pengolahan data menggunakan Software smart PLS SEM (Partial Least Square – Structural Equation Modeling). Hasil penelitian menunjukkan bahwa resiliensi, job security, kepemimpinan, dan kepuasan kerja memiliki pengaruh signifikan terhadap turnover intention pada karyawan Generasi Z, di mana karyawan dengan tingkat resiliensi yang tinggi, rasa aman dalam pekerjaan, dukungan dari pemimpin yang efektif, serta kepuasan kerja yang memadai cenderung memiliki intensi keluar yang lebih rendah. Implikasi praktis dari penelitian ini adalah bahwa organisasi perlu mengembangkan program yang berfokus pada pengembangan resiliensi, kepemimpinan efektif, dan kepuasan kerja, serta memastikan adanya jaminan pekerjaan yang jelas untuk meningkatkan retensi karyawan dan produktivitas jangka panjang.